Comparison of Immunotherapy, Chemotherapy, and Chemoimmunotherapy in Advanced Pulmonary Lymphoepithelioma-Like Carcinoma： A Retrospective Study - Xiao, Yi; He, Jinyuan; Luo, Shaoning; Dong, Min; Li, Wei; Liu, Gaijiao; Chen, Hongjie; Yang, Xiongwen; Huang, Shaohong (Frontiers in Oncology, 2022)
Pulmonary lymphoepithelioma-like carcinoma (pLELC) is a rare subtype of lung cancer that is associated with the Epstein-Barr virus in Asia. Due to the lack of prospective studies, the best first-line treatment and survival outcomes remain unclear. Herein, This study investigated the efficacy and safety of different treatment regimens for advanced pLELC. This retrospective study included 68 patients with advanced pLELC from two centers in China. Patients were divided into three groups according to different first-line treatments: chemotherapy (n=49, 72.1%), immunotherapy (n=7, 10.3%), and chemoimmunotherapy (n=12,17.6%). The primary endpoint of this study was the 2-year progression-free survival (PFS) of each group. The results show that the median PFS was 6.9 months (range, 2.3–not estimable) in the chemotherapy group, 11.0 months (range, 2–not estimable) in the immunotherapy group, and 11.8 months (range, 6–not estimable) in the chemoimmunotherapy group. There was a significant difference in 2-year PFS between the chemoimmunotherapy group and the chemotherapy group (hazard ratio, 0.38, 95% confidence interval: 0.18-0.78, log-rank P=0.007). The most frequent grade 3-4 adverse event in the chemotherapy and chemoimmunotherapy groups was myelosuppression (10/49 [22.4%] and 4/12 [33.3%], respectively). The most frequent grade 3-4 adverse events in the immunotherapy group were diarrhea (1/7, 14.8%) and hepatotoxicity (1/7, 14.8%). Chemoimmunotherapy had the highest 2-year PFS as a first-line treatment for advanced pLELC compared to chemotherapy and immunotherapy. This study suggests that chemoimmunotherapy may be the best first-line treatment for patients with advanced pLELC.